Solve the following system of equation by the method of cross-multiplication:

Asked by nkrbasak | 21st Sep, 2010, 11:25: AM

Expert Answer:

Multiply (1) equation by (a - 2b) and (2) by (a + 2b),
(a-2b)(a+2b)x + (a-2b)(2a-b)y = 2(a-2b)
(a-2b)(a+2b)x + (a+2b)(2a+b)y = 3(a+2b)
and subtract, we get,
[(a-2b)(2a-b) - (a+2b)(2a+b)]y = 2(a-2b) - 3(a+2b)
[(a-2b)(2a-b) - (a+2b)(2a+b)]y = 2(a-2b) - 3(a+2b)
-10aby = - a - 10b
y = (a + 10b)/ab.
Substituting this back in (1) or (2) we can get x.
Regards,
Team,
TopperLearning.
 

Answered by  | 21st Sep, 2010, 11:23: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.